2017
DOI: 10.1177/1524839917707791
|View full text |Cite
|
Sign up to set email alerts
|

C-SAFE: A Computer-Delivered Sexual Health Promotion Program for Latinas

Abstract: This article describes the development and evaluation of C-SAFE (Sexual Awareness for Everyone), a computer-delivered sexual health promotion program for Latinas. We first describe the process of adapting an evidence-based, group-level intervention into an individually administered computer-delivered program. We then present the methods and results of a randomized control trial with 321 Latinas in California and Florida to test C-SAFE’s preliminary efficacy in reducing sexual health risk. We found no statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Studies reported (in descending order of frequency) on anxiety features (87 articles; 29.5%), affective symptoms (65 articles; 22.0%), other emotional and behavioral problems (62 articles; 21.0%), conduct problems (59 articles; 20.0%), general psychological distress (52 articles; 17.6%), alcohol use (42 articles; 14.2%), externalizing behaviors, (31 articles; 10.5%), tobacco use (32 articles; 10.8%), internalizing behaviors (25 articles; 8.5%), cannabis use (23 articles; 7.8%), ADHD features (21 articles; 7.1%), interpersonal violence (14 articles; 4.7%), eating-related problems (13 articles; 4.4%), consequences of alcohol use (12 articles; 4.1%), PTSD features (6 articles; 2.0%), sleep-related problems (6 articles; 2.0%), and impaired functioning (5 articles; 1.7%) (Supplemental Table 3, http://links.lww.com/HRP/A158). 44–133, 134–231, 232–332 …”
Section: Resultsmentioning
confidence: 99%
“…Studies reported (in descending order of frequency) on anxiety features (87 articles; 29.5%), affective symptoms (65 articles; 22.0%), other emotional and behavioral problems (62 articles; 21.0%), conduct problems (59 articles; 20.0%), general psychological distress (52 articles; 17.6%), alcohol use (42 articles; 14.2%), externalizing behaviors, (31 articles; 10.5%), tobacco use (32 articles; 10.8%), internalizing behaviors (25 articles; 8.5%), cannabis use (23 articles; 7.8%), ADHD features (21 articles; 7.1%), interpersonal violence (14 articles; 4.7%), eating-related problems (13 articles; 4.4%), consequences of alcohol use (12 articles; 4.1%), PTSD features (6 articles; 2.0%), sleep-related problems (6 articles; 2.0%), and impaired functioning (5 articles; 1.7%) (Supplemental Table 3, http://links.lww.com/HRP/A158). 44–133, 134–231, 232–332 …”
Section: Resultsmentioning
confidence: 99%
“…The need to pay attention to nativity and subgroup or regional affiliation among Latinos is particularly important in light of other studies that show that the internet is becoming the most common source of health information for all ethnic groups [38]. In addition, although emerging research shows that Spanish speakers view Web-based health portals positively [39] and computer-assisted interventions are being deployed more frequently among US Latinos [40], our research implies that the deployment of such interventions online will have uneven penetration among Latinos, particularly foreign-born individuals and Mexican-identified persons. Our findings also support previous research showing that certain portions of the US Mexican-identified population, such as farmworkers, do not seek health information online [36].…”
Section: Discussionmentioning
confidence: 99%
“…We also conducted a third post-hoc analysis to see nativity was a significant predictor of online HISB and HIT use among Within group nativity differences: We then examined online health information seeking behavior among Mexican-identified individuals to understand differences in online HISB and HIT use by nativity. We found that US-born individuals had higher odds (OR=1.9, 95% CI: 1.6, Additionally, while emerging research shows that Spanish speakers view online health portals positively, [28] and computer assisted interventions are being deployed more frequently among US Latinos, [29] our research implies that the deployment of such interventions online will have uneven penetration among Latinos, particularly foreign born individuals and Mexican-identified persons. Our findings also support previous research…”
Section: Resultsmentioning
confidence: 47%